Applications of cerebrospinal fluid circulating tumor cells and circulating tumor-derived DNA in diagnosis, prognosis, and personalized treatment of CNS metastases - Pentsova, Elena (Frontiers in Oncology, 2024)
A common feature of advanced solid tumors is their ability to metastasize and colonize distant organs, including the Central Nervous System (CNS), which encompasses brain and leptomeningeal metastases (LM). While cerebrospinal fluid cytopathological analysis remains a gold standard diagnostic tool, it only provides limited insights into the biology of tumor cells; thus, it is urgent to develop minimally invasive biomarkers that enable a comprehensive quantitative and molecular characterization of disseminated cells, therapy response assessment, and disease monitoring. Liquid biopsy methods have been swiftly developed for some readily accessible bodily fluids such as plasma and urine; circulating tumor cells (CTCs) and circulating tumor DNA (ctDNA) from these sources have been rapidly implemented into clinical trial design, disease monitoring, and treatment assignment across different tumor types. However, the filter imposed by the brain blood barrier (BBB) hampers the release of tumor-derived cells and molecules from CNS metastases. Crucially, cerebrospinal fluid (CSF) liquid biopsy methods offer a unique and unparallel source to develop liquid biopsy methodologies in patients with CNS-disseminated disease, including the characterization of CTCs and ctDNA arising specifically from brain and leptomeningeal metastasis. These technologies have enabled a deeper understanding of tumor cell and molecular dynamics, including the reconstruction of clonal evolution in the brain microenvironment through longitudinal sapling. Here, we discuss the current challenges and opportunities that CSF liquid biopsy methods face for the implementation of these approaches into clinical settings.